Comprehensive Survey of Routing Techniques in Wireless Sensor Network (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Wireless Sensor Netw orks ( WSNs) c onsist of small nodes with sensing, computation, and wireless communications capabilities. Many routing, power management, and data dissemination protocols have been specifically designed for WSNs where energy awareness is an essential design issue. The focus , however, has been given to the routing protocols which might differ depending on the application and netw ork architecture. In this paper, we present a survey of the state-of-the-art routing techniques in WSNs. We first outline the designchallenges for routing protocols in WSNs followed by a comprehensive survey of different routing techniques . Overall, the routing techniques are classified into three categories based on the underlying netw ork structure: flat, hierarchical, and location-based routing. Furthermore, these protocols can be classified into multipath-based,query-based, negotiation-based, QoS-based, and coherent-based depending on the protocol operation. We study the design tradeoffs b e twe e n ener gy and communication overhead savings in every routing paradigm. We also highlight the adv antages and performance issues of each routing technique.